Studies on fortification in India - Jean Deloche (Institut Français de Pondichéry, 2007)
This book brings together essays on some prominent defensive works which have been constructed over many centuries across the Indian subcontinent, particularly South India. The first chapter, on the Harappan period and Early Historic Indian sites, is based mainly on archaeological reports; all the other chapters, covering South India from the 3rd to the 18th century A.D., draw on the available historical material, both documentary and epigraphic, as well as on intense field work and personal investigations carried out by the author over the past twenty years in numerous hill forts and fortified towns in India. Much of the information has been already published piecemeal in a range of articles written in French. Here, the findings of this body of work are freshly presented with an attempt at synthesis. For each period a selection has been made of outstanding examples of fortification in order to analyse the building techniques, considering the evolution of military technology, particularly the development of artillery, to establish the typology of the structures and to bring into focus a reliable method for identifying and dating defensive works in India. This analysis, which draws attention to the considerable skills and ingenuities of Indian fort builders, has something to engage the interest of all those concerned with India military monuments, be they engineers, archaeologists or historians.